Impact of retroflexion in the right colon after repeated forward‐view examinations. Issue 6 (10th September 2018) - Miyamoto, Hideaki; Naoe, Hideaki; Oda, Yasushi; Shono, Takashi; Narita, Rei; Oyama, Shinichiro; Hashigo, Syunpei; Okuda, Ayako; Hasuda, Kiwamu; Tanaka, Motohiko; Sakurai, Kouichi; Murakami, Yoshitaka; et al.
Abstract : Background and Aim: Right colon polyps can especially be overlooked when they are located on the backs of haustral folds. Previous studies have reported that repeated forward‐view examinations in the right colon were effective in reducing adenoma miss rates. The aim of this study was to clarify the impact of retroflexion in the right colon after repeated forward‐view examinations. Methods: This multicenter, prospective, observational study was conducted at three institutions in Kumamoto, Japan, between February 2014 and December 2015. Subjects who were over 40 years old and scheduled for colonoscopy were recruited. For the forward view, after cecal intubation, the colonoscope was withdrawn to the hepatic flexure. The colonoscope was sequentially reinserted to the cecum and then withdrawn to the hepatic flexure. For the retroflexion view (RV), the colonoscope was reinserted to the cecum, retroflexed, and then withdrawn to the hepatic flexure. All polyps were resected at the time of detection. The primary outcome of this study was the adenoma miss rate for the repeated forward‐view examinations. Results: Of the 777 enrolled participants, retroflexion was successful in 730 (94.0%). The repeated forward‐view withdrawal technique detected 291 adenomas, while the third withdrawal in the RV detected 53. The adenoma miss rate for the repeated forward‐view withdrawal was 15.4%. No severe adverse events occurred during retroflexion. Conclusion: Because adenomas located on potential blind spots can be missed when only using forward‐view examinations, retroflexion in the right colon after repeated forward‐view examinations might improve colonoscopy detection rates. Abstract : This prospective observational study highlights the importance of retroflexion in right colon. We performed retroflexion in right colon after repeated forward view examinations, and retroflexion view yielded an additional 15.4% of the adenomas and 18.6% of the advanced neoplasm without a severe adverse event. Retroflexion should be recommended as a way of improving the overall quality of the examination and for helping to safely detect and prevent CRC.